Foreign trade and economic development of underdeveloped countries - Sachs, Ignacy (New York : Asia Pub. House, 1965)
The book is meant to present an analysis of the role of the less developed countries in the international division of labour, paying special attention to the impact of the crisis of the traditional international division of labour on the development prospects of the countries of Asia, Africa, and Latin America, and the prospects of expanding the economic relations between Poland and the developing countries.
rpm 23/01/2019
Loans
Keywords: Economic development; Commerce; Developing countries